Biological Profile of Synthetic and Natural Indole Derivatives: Paving New Paths in Cancer Treatment - Ana Margarida Janeiro; Carolina S. Marques (MDPI AG, 2024)
The indole scaffold is considered a privileged framework in the design and synthesis of several active pharmaceutical ingredients, particularly as promising anticancer agents. Its presence in several bioactive natural compounds has caught the attention of the scientific community, which has been committed to unveiling its biosynthetic pathways and generating multiple derivatives with innovative synthetic routes. The large variety of structural derivatives enhances their use in multiple bioapplications and pharmacological activities. In this review, the reader will have easy access to some examples of natural and synthetic indole derivatives with antimicrobial, antidepressant, anti-inflammatory, antiviral, antimigraine, and antiemetic activity. However, the main topic of this review is related to cancer and the importance of indole derivatives as promising anticancer drugs. Two of the reasons why cancer is considered a massive problem worldwide are attributed to the struggle to develop target-specific drugs while avoiding drug resistance. Among countless drugs targeting specific proteins involved in tumorigenesis, prompting life quality in the treatment of several cancer types, protein kinases, desoxyribonucleic acid topoisomerases, and P-glycoprotein have been shown to be the main targets when it comes to the development of novel anticancer agents. Furthermore, indole and its derivatives are also studied regarding affinity to other targets related to cancer. This review aims to highlight the utility of the indole scaffold in anticancer drug design, inspiring the creation and synthesis of new derivatives that target specific proteins and address drug resistance challenges.